The Effect of Outdoor Activity Learning Model on Learning Motivation in Terms of Responsibility and Cooperation of Elementary School Students - Esim Esim; Maulidin Maulidin; Mujriah Mujriah; Ali Muhaimin; Lalu Hulfian (Journal Of Sport Education (JOPE), 2025)
This study aimed to analyze the effect of the outdoor activity learning model on elementary school students’ learning motivation in terms of responsibility and cooperation. This research employed an experimental method with a 2×2 factorial design. The sample consisted of 48 elementary school students selected using stratified purposive sampling. Research instruments included questionnaires on learning motivation, responsibility, and cooperation, which had been tested for validity and reliability. Data were analyzed using two-way analysis of variance (ANOVA). The results indicated significant differences in learning motivation between students with high and low levels of responsibility, as well as between students with high and low levels of cooperation. Furthermore, there were interaction effects between the outdoor activity learning model, responsibility, and cooperation on students’ learning motivation. It can be concluded that the outdoor activity learning model is effective in enhancing PJOK learning motivation while fostering responsibility and cooperation among elementary school students.